The study of road pavement performance through impact hammer tests - Praticò, Filippo G.; Pellicano, Gianfranco; Fedele, Rosario (International Conference “Environmental Engineering”, 2020)
Noise pollution has become an important issue. One of the main sources of noise in residential areas is represented by transportation and by the interaction between tyre and road surface. Several studies illustrate that traffic noise is affected by road properties such as acoustic absorption, surface texture, and mechanical impedance. This latter, function of the angular frequency ω, is defined as the ratio of a force applied on a structure to the induced velocity. Despite a growing interest in mechanical impedance there is still lack of results about its impact on traffic noise. Consequently, the aim of the study presented in this paper is to investigate the relationship between road acoustic response and mechanical impedance. Tests (EN 29052-part 1, ISO 7626-5) have been performed on different types of samples and materials, using an impact hammer and an accelerometer. Investigations are still in progress. First results seem to demonstrate that both frequencies and other noise-related characteristics could be affected by changes of mechanical impedance, boundary conditions, tests, and type of material.